Approaching the Arctic: the occurrence of Parin’s spinyfin Diretmichthys parini (Beryciformes: Diretmidae) in the Nordic Seas - Lynghammar, Arve; Byrkjedal, Ingvar; Bugjerde, Berit Margrete; Wienerroither, Rupert (Fauna norvegica, 2020)
Two adult specimens of the tropical to subtropical fish species Diretmichthys parini are reported from the North Sea and the northern Norwegian Sea, respectively. Both were accidentally caught as bycatch by commercial trawlers. Although not uncommon in Icelandic waters, it has not been documented from the Nordic Seas previously. In light of the major currents and water temperatures in the area, this is puzzling. Whether this pattern reflects a true distributional change or increased awareness and reporting from fishermen is not known.